74.6k views
0 votes
Solve the following equation show your work 3{-x + (2x + 1)} = x - 1

2 Answers

1 vote

Answer:

x = -2

Explanation:

For this problem, we must simply solve for x. To do this, we will need equation operations, and the use of the distributive property.

Let's work this line by line until we have the value for x:

3{-x + (2x + 1)} = x - 1

3*-x + 3*(2x + 1) = x - 1

-3x + 6x + 3 = x - 1

3x + 3 = x - 1

2x = -4

x = -2

Now we can check our answer for x by plugging back into the original equation and see if the left hand side is equal to the right hand side:

3{-x + (2x + 1)} = x - 1

3{-(-2) + (2(-2) + 1)} ?= (-2) - 1

3{2 + (-4 + 1)} ?= -3

3{2 + (-3)} ?= -3

3{-1} ?= -3

-3 == -3

Thus, we have found the solution for x to be equivalent to negative 2.

Cheers.

User Xi Vix
by
4.9k points
1 vote

Answer:

x = - 2

Explanation:

3{-x + (2x + 1)} = x - 1

First solve the terms in the bracket first

That's

3 (- x + 2x + 1 ) = x - 1

3( x + 1) = x - 1

Expand the terms in the bracket

We have

3x + 3 = x - 1

Simplify

3x - x = - 1 - 3

2x = - 4

Divide both sides by 2

We have the final answer as

x = - 2

Hope this helps you

User KCzar
by
4.6k points